Dermatoscopic patterns of cutaneous metastases: a multicentre cross-sectional study of the International Dermoscopy Society - Tiodorovic, Danica; Stojkovic-Filipovic, Jelena; Marghoob, Ashfaq; Argenziano, Giuseppe; Puig, Susana; Malvehy, Josep; Tognetti, Linda; Pietro, Rubegni; Akay, Bengu Nisa; Zalaudek, Iris; Hänßle, Holger; Müller-Christmann, Christine; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
Background The detection of cutaneous metastases (CMs) from various primary tumours represents a diagnostic challenge. Objectives Our aim was to evaluate the general characteristics and dermatoscopic features of CMs from different primary tumours. Methods Retrospective, multicentre, descriptive, cross-sectional study of biopsy-proven CMs. Results We included 583 patients (247 females, median age: 64 years, 25%-75% percentiles: 54-74 years) with 632 CMs, of which 52.2% (n = 330) were local, and 26.7% (n = 169) were distant. The most common primary tumours were melanomas (n = 474) and breast cancer (n = 59). Most non-melanoma CMs were non-pigmented (n = 151, 95.6%). Of 169 distant metastases, 54 (32.0%) appeared on the head and neck region. On dermatoscopy, pigmented melanoma metastases were frequently structureless blue (63.6%, n = 201), while amelanotic metastases were typified by linear serpentine vessels and a white structureless pattern. No significant difference was found between amelanotic melanoma metastases and CMs of other primary tumours. Conclusions The head and neck area is a common site for distant CMs. Our study confirms that most pigmented melanoma metastasis are structureless blue on dermatoscopy and may mimic blue nevi. Amelanotic metastases are typified by linear serpentine vessels and a white structureless pattern, regardless of the primary tumour.